Repertoire of BALB/c Mice Natural Anti-Carbohydrate Antibodies: Mice vs. Humans Difference, and Otherness of Individual Animals - Bello-Gil, Daniel; Khasbiullina, Nailya; Shilova, Nadezhda; Bovin, Nicolai; Mañez, Rafael (Frontiers in Immunology, 2017)
One of the most common genetic backgrounds for mice used as a model to investigate human diseases is the inbred BALB/c strain. This work is aimed to characterize the pattern of natural anti-carbohydrate antibodies present in the serum of 20 BALB/c mice by printed glycan array technology, and to compare their binding specificities with that of human natural anti-carbohydrate antibodies. Natural antibodies from the serum of BALB/c mice interacted with 71 glycans from a library of 419 different carbohydrate structures. However, only seven of these glycans were recognized by the serum of all the animals studied, and other five glycans by at least 80% of mice. The pattern of the 12 glycans mostly recognized by the circulating antibodies of BALB/c mice differed significantly from that observed with natural anti-carbohydrate antibodies in humans. This lack of identical repertoires of natural anti-carbohydrate antibodies between individual inbred mice, and between mice and humans, should be taken into consideration when mouse models are intended to be used for investigation of natural antibodies in biomedical research.